The implication of research methods on agricultural policy development: A case study of South African land redistribution - Olubode-Awosola, O. O.; Schalkwyk, H.D. van (2007)
The ineffectiveness of policy advice in most African countries could be attributed to problem of scientists not being able to present a holistic solution to policy problems. As a result, the consequences of policies are seldom indicated. It may be demanding to use a more comprehensive and quantitative research strategy in policy analysis because of limited ability to integrate the technical-biophysical with the economic, marketing and political aspects when analysing policy effects. To exemplify this phenomenon, a forward-looking and prescriptive economic analysis that is being widely used in the developed world for agricultural policy analysis at each country's level; integrated development at regional level; and competitive participation in the globalisation, was adopted. The study examines the potential effects of the South African land redistribution strategies on its agriculture using a mathematical programming model for an agricultural sector. This study makes a contribution to land redistribution policy, which is presently not only one of the most definitive political and development issues, but also perhaps the most intractable in South Africa. The results indicate that the current policy requires more economic imperatives, as it tends towards smallholder agriculture that cannot produce adequate yields to meet either domestic demand or a tradable volume. The current land redistribution, though justifiable, may have adverse supply impacts if pursued too rapidly and inflexibly because it places the South African farm industry on an inefficient growth trajectory. This is because multiplying the number of small farm units has a negative implication for the Southern African Development Community (SADC)'s agricultural productivity and competitiveness in the global market as South Africa is the largest economy not only in the SADC region but also Africa. Given the challenges of a free market and the fact that the settled small-scale resource- poor (mainly black) farmers are less efficient compared to the large-scale (mainly white) farmers from whom government transfers land, the study prescribes land redistribution strategies that consider efficiency along with equity. The study further suggests that agricultural land can act as a safety net for the poor, where the efficiency argument does not hold.